Etioclinical profile and outcome of acute bacterial meningitis in post neo natal U-5 children: a study from tertiary care center of coastal Odisha, India - Mohanty, Niranjan; Biswas, Tapan Kumar; Satapathy, Smita; Meher, Shantanu Kumar; Patro, Debasis (International Journal of Research in Medical Sciences, 2017)
Background: Acute bacterial meningitis (ABM) continues to remain an important cause of morbidity, mortality and handicap in children despite availability of wide range of antimicrobials. The microorganisms vary according to age, socio economic condition and geographical area along with other factors. Methods: A prospective study was conducted over 2.5 years from October 2012 to April 2015 in the department of pediatrics, SVP Institute of Pediatrics, SCB Medical College, Cuttak, Odisha, India. Total 104 subjects were included after taking meticulous inclusion criteria. Results: Out of 104 cases, majority (70.2%) were infants. 60.6% were male with M:F ratio 1.5:1. Fever was the commonest symptom in 69.2% followed by convulsion 61.5%, vomiting 36.5%, altered sensorium 33.7%. On examination 69.2% children were febrile, having bulging fontanelle in 34.6%, pneumonia 31.7%, positive meningeal sign 29.8%, cranial nerve palsies 14.4%, papilledema 12.5% and hemiplegia 11.5% cases. GCS were poor (<7) in 26.9% cases. 33.6% had high CSF cell count (>100/cumm). In 82 cases (78.8%) etiological agents were identified consisting of H. influenzae in 46.4%, S. pneumoniae in 36.6%, E. coli in 8.6% and others in 8.4%. CT scan of brain revealed brain edema in 29.4% followed by subdural effusion 19.6%, hydrocephalus 17.6% and infarction in 5.9%. 63.5% children were recovered completely. Mortality was 16.3% with sequelae in 20.2% cases. Conclusions: Hib and Pneumococci were two most common organisms causing ABM in U-5 children with high mortality and sequelae which can be prevented by early diagnosis, optimum lab diagnostic facility and mass vaccination. There is urgent need to include Pneumococcal vaccine in NIP for substantial reduction of infant mortality.